A characterization for the flow behavior of as-extruded 7075 aluminum alloy by the improved Arrhenius model with variable parameters - Quan,Guo-zheng (2013)
In order to perform the numerical simulations of forging response and establish the processing parameters for as-extruded 7075 aluminum alloy, the compressive deformation behavior of as-extruded 7075 aluminum alloy were investigated at the temperatures of 573 K, 623 K, 673 K and 723 K and the strain rates of 0.01 s-1, 0.1 s-1, 1 s-1 and 10 s-1 on a Gleeble1500 thermo-mechanical simulator. Based on the analysis of the effect of strain, temperature and strain rate on flow stress, dynamic recrystallization (DRX) type softening characteristics of the stress-strain curve with single peak were identified. The traditional Arrhenius type model is in favor of the prediction for the flow stress at a fixed strain, and can not satisfy the need of the numerical simulations of various hot forming processes due to the lack of the effect of strain on flow stress. Lin et al. improved Arrhenius type model with a series of variable coefficients as functions of true strain (including activation energy of deformation Q, material constants n and a, and structure factor A) to predict the flow stress during the hot compression. The application has been demonstrated in this work for as-extruded 7075 aluminum alloy. The comparisons between the predicted and experimental results show that, for the worst case, the error in the flow stress estimate is 5.63%, and the max mean error is 3.6%. The developed model provides fast, accurate and consistent results, making it superior to the conventional Arrhenius type model. In further it can be used in computer code to model the forging response of 7075 aluminum alloy mechanical part members under the prevailing loading conditions.